Results of treatment of disseminated breast cancer carried out in Greatpoland Cancer Center - O’Shea, Agnieszka; Jezierska, Dorota; Nowakowska, Elżbieta; Bąk, Grażyna; Skowronek, Janusz; Adamska, Krystyna; Kubaszewska, Maria (Contemporary Oncology/Współczesna Onkologia, 1999)
Breast cancer in stage M1 is uncurable. It is, however, important to point out that in some patients the disease can be controlled for many years using chemotherapy or hormonotherapy connected with radiotherapy. 92 patients with metastatic breast cancer were treated in Greatpoland Cancer Center from 1983 to 1987. Patients age at the time of first diagnosis ranged from 29 to 74 years, median was 51,5. At the time of occuring of metastases median age was 56,4. Methods of treatment included chemo or hormonotherapy and radiotherapy in different combinations. 5-years survival rate was 7,6% after recognising of metastases. Median survival time in whole group was 13,5 months. Survival time in 67,4% of patients was shorter than 2 years. In 70,7% of cases (69/92) metastases occured in first 5 years after the end of treatment of primary lesion, in 67,0% they occured in first 3 years. In 27 cases (29,3%) metastases occured after 5 years of observation. In group of 34 patients with 4 or more involved axilla lymph nodes only in 4 cases (11,8%) asymptomatic survival time was longer then 5 years. In 10 cases of 22 patients (45,5%) with non involved axilla lymph nodes metastases occured after 5 years of observation. The most frequent location of metastases were bones. These patients had greater probability for longer asymptomatic survival time.